ANALYSIS ON FACTORS AFFECTING THE PARTICIPATION OF MARRIED WOMEN IN INFORMAL SECTOR (Case studyonTheTradersin Ketawang Gede Sub-district, Malang) - Fika Sumule; Wildan Syafitri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study analyzes factors affecting the participation of married women (in the age of 16-60 years) in informal sector in Ketawang Gede sub-district, Malang. Using Linear Probability Model and Logit Model on 50 respondents, this study reveals migrationstatus, total working hours/day, number of dependent, level of income and husband’s employment status significantly affect the participation of married women in informal sector. On the other hand, age and education have no significant effect on participation of married women. Marital status has a significant role in affecting the decision of women for working in formal or informalsector. However, since informal activity can accommodate the family responsibility, married woman prefer to join in informal sector.Keywords: Participation of married women, Informal Sector.